Microsatellite analysis of genetic population structure of the endangered cyprinid Anaecypris hispanica in Portugal: Implications for conservation - salgueiro, P.; Carvalho, G.; Collares-Pereira, M.J.; Coelho, M.M. (Biological Conservation, 2003)
The endangered fish species Anaecypris hispanica is restricted to eight disjunct populations in the Portuguese Guadiana drainage. The genetic structure of these populations was studied in order to determine levels of genetic variation within and among populations and suggest implications for conservation of the species. Based on five microsatellite loci, the null hypothesis of population homogeneity was tested. Tests for genetic differentiation revealed highly significant differences for pairwise comparisons between all populations, and substantial overall population subdivision (FST=0.112). All sampled populations contained unique alleles. Our findings indicate marked genetic structuring and emphasise limited dispersal ability. The high levels of genetic diversity detected within and among A. hispanica populations suggest, however, that the observed fragmentation and reduction in population size of some populations during the last two decades, has impacted little on levels of genetic variability. Data imply that most A. hispanica populations should be managed as distinct units and that each has a high conservation value containing unique genetic variation. It is argued that geographic patterns of genetic structuring indicate the existence of eight management units.